COMPARISON OF DARK AND MILK COCOA TOPPINGS PRODUCED BY A FIVE-ROLL MILL AND A BALL MILL - Stožinić, Milica; Popović, Tijana; Lončarević, Ivana; Pajin, Biljana; Zarić, Danica; Nikolić, Ivana; Petrović, Jovana (Food and Feed Research, 2024)
Chocolate toppings are confectionery products comprised of non-fat dark cocoa solids and sugar particles dispersed in cocoa butter, as a continual matrix. On the other hand, dark cocoa toppings contain cocoa powder and sugar dispersed in vegetable fat that is cheaper than cocoa butter, but with adequate characteristics. Also, with the addition of a 7% non-fat milk fraction, this product is regarded as a milk cocoa topping. This kind of product, dark and milk cocoa toppings, does not demand long-term conching or tempering. This study aimed to determine and compare the impact of the production process on rheology, particle size distribution and content of moisture, fats, sucrose and lactose. Based on the rheology properties, it was found that the values of the Casson and linear viscosity of the samples produced using a five-roll mill and conching were lower compared to those produced using a ball mill. Regarding particle size distribution, the results showed that the volume-weighted mean parameter D (4,3) was lower for the milk and dark cocoa confectionery topping produced in the ball mill. Additionally, the values of the yield stress in samples produced in the ball mill were 2-fold higher for the milk cocoa topping and 4.5-fold higher for the dark cocoa topping compared with the values of the samples produced using the five-roll mill and conching. The near-infrared spectroscopy (NIRS) analysis did not show any significant difference among the samples. It can be concluded that the difference between the samples produced in the ball mill and the five-roll mill and conching exists and that the ball mill can be used for the production of high-quality cocoa toppings thus providing a shorter time of production.